Media Edukasi Tumbuh Kembang Bayi 0 – 12 Bulan di Wilayah Kerja Puskesmas Tangerang Selatan - Alamsyah, Chairunnisa Minarni; Kusumadewi, Feny; Octasila, Restu (Jurnal Kebidanan Malakbi, 2022)
The motor development of children in Indonesia is relatively low, based on the Center for Nutrition Research and Development of the Ministry of Health of the Republic of Indonesia in 2012, the results of the Denver Development Screening Test (DDST) II survey found that the prevalence of fine and gross motor disorders in toddlers was 25%, or every 2 out of 1,000 toddlers had motor developmental disorders. Based on Riskesdas 2013 there were 14 million children who experienced emotional development disorders. Toddler period is an important because this period is a critical for memory development to get to know something, so the right stimulus is needed so that the potential of children develops optimally.The purpose of this research is to develop and design educational media for the growth and development of children aged 0 – 12 months. This research was conducted in 2 stages. The first stage is to analyze the understanding of the mother's condition and needs regarding information on growth and development of babies aged 0-12 months, and the compilation of an educational media that can be used to provide a good and easy-to-understand understanding according to the mother's needs, the second stage is the stage of testing the information media . The sample of this research is mothers who have babies aged 0 – 12 months, the test carried out is T-Test Dependent. The results of the study, most of the respondents had a high school education background (52.9%), most of the respondents had more than one child (76.5%) with good socio-economic conditions (70.6%). The results of the statistical test obtained a P Value of 0.001 > (0.05) meaning that there was a significant difference in mother's knowledge about infant growth and development before and after being given the child's PANTASI educational media.